Fecal microbiota transplantation in a rodent model of short bowel syndrome: A therapeutic approach? - Fourati, Salma; Dumay, Anne; Roy, Maryline; Willemetz, Alexandra; Ribeiro-Parenti, Lara; Mauras, Aurélie; Mayeur, Camille; Thomas, Muriel; Kapel, Nathalie; Joly, Francisca; Le Gall, Maude; Bado, André; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
Extensive intestinal resection leads to Short Bowel Syndrome (SBS), the main cause of chronic intestinal failure. Colon preservation is crucial for spontaneous adaptation improving absorption and reducing parenteral nutrition dependence. Fecal microbiota transplantation (FMT), a promising approach in pathologies with dysbiosis as the one observed in SBS patients, was assessed in SBS rats with jejuno-colonic anastomosis. Weight evolution, food intake, and microbiota composition of Sham and SBS rats transplanted or not with high fat diet rat microbiota were analyzed. FMT modified microbiota alpha- and beta-diversity in control but not SBS rats. Microbiota composition of SBS rats, transplanted or not, was largely enriched with lactobacillus, and alpha- and beta-diversity were very different from that of controls. FMT was successful in control but failed in SBS rats, probably because of the specific luminal environment in colon of SBS subjects favoring aero-tolerant over anaerobic bacteria. Microbiota composition of SBS rats, transplanted or not, was largely enriched with lactobacillus, and alpha- and beta-diversity were very different from that of controls. Besides, food intake was positively correlated with Lactobacillaceae. Microbiota transfer must be optimized and adapted to this specific SBS environment.